2019
DOI: 10.1055/s-0039-1688408
|View full text |Cite
|
Sign up to set email alerts
|

Direction of Flap Rotation in Propeller Flaps: Does It Really Matter?

Abstract: The use of perforator flaps has steadily increased since the introduction of the concept by Koshima and Soeda. 1-3 The perforator flaps offer the advantages of sparing the underlying muscle, resulting in decreased donor-site morbidity. Hyakusoku et al first used the term "propeller flap" in 1991, to describe subcutaneous pedicled island flaps vascularized by a perforator artery and rotated 90°to reconstruct the defect after release of scar contractures in a burn patient. 4 Once a propeller flap has a reliable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…17 However, Song et al have used color duplex ultrasound flow dynamics to show that the choice with higher perforator flow volume and flow velocity will have fewer untoward events. 18 Another option available is to use smartphone thermal imaging after any component flap rotation to assess surface temperature, which is directly correlated to flap perfusion as demonstrated in another overview in this issue. 19…”
Section: Discussionmentioning
confidence: 99%
“…17 However, Song et al have used color duplex ultrasound flow dynamics to show that the choice with higher perforator flow volume and flow velocity will have fewer untoward events. 18 Another option available is to use smartphone thermal imaging after any component flap rotation to assess surface temperature, which is directly correlated to flap perfusion as demonstrated in another overview in this issue. 19…”
Section: Discussionmentioning
confidence: 99%
“…For darker pigmented individuals, thermography would be a better option as color assessment alone may be difficult. Song et al 19 have used color Duplex ultrasound to obtain physiologic flow data on pedicle flow and volume following the rotation. They concluded that if the direction with higher values is always chosen, no major complications will occur, whereas if based solely on clinical signs in their experience, total flap loss or partial necrosis was a risk that can now be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…11,34,35 Color duplex ultrasound in addition allows measurement of the perforator diameter and the velocity of blood flow, especially for comparison if multiple perforators are available [36][37][38][39][40][41] or deciding whether a clockwise or counterclockwise twist should be performed. 42 Some even prefer high-resolution CT scans for more accuracy not only in identifying perfora-tors but also in providing reliable perforators, especially if trauma or peripheral vascular disease coexist. 43,44 Magnetic resonance angiography also may be an alternative, 9,45 but a simpler, readily available complementary method such as thermography can be an option by using a thermal imaging camera attached to a smartphone.…”
Section: Methodology Preoperative Identification Of Perforatorsmentioning
confidence: 99%